Sound Absorption Performance Of Natural Fiber Composite From Chrome Shave And Coffee Silver Skin - Monazzam, Mohammadreza; Putra, Azma; Abdi, Debelo Dugasa; Taban, Ebrahim; Golbabaei, Farideh; Khadem, Monireh (Elsevier Ltd., 2021)
This paper presents the sound absorption performance of natural fiber composites developed from chrome shave (CS) and coffee silver skin (CSS). Twelve test samples of thickness 30 mm and 50 mm were fabricated with different fiber sizes and fiber ratios and by maintaining the density of the samples by 150 kg/m3. Normal incidence sound absorption coefficient spectra were measured in an impedance tube. Absorption coefficient spectra were predicted using the Johnson-Allard-Champoux (JCA) model using best fit values of tortuosity and the two characteristic lengths together with measured values of porosity and flow resistivity. The results revealed that the CS-CSS composite had average absorption coefficient of 0.95 above 1 kHz for a thickness of 30 mm and 50 mm. 'The predictions and data are in good agreement up to 6 kHz.